Immunogenic properties of octasaccharide-protein conjugates derived from Klebsiella serotype 11 capsular polysaccharide. - Zigterman, J W (1985)
The tetrasaccharide repeating unit of the capsular polysaccharide of Klebsiella serotype 11, K11PS, comprises the following sequence: [----3)-beta-D-GlcpA-(1----3)-alpha-D-Galp-(1----3)-beta-D-Glcp-(1 ----] with a 4,6-O-(1-carboxyethylidene)-alpha-D-galactopyranosyl residue linked to O-4 of the glucuronic acid residue. Octasaccharide (OS) derived from K11PS by bacteriophage phi 11-associated glycanase, was coupled to bovine serum albumin and to keyhole limpet hemocyanin. The immunogenicity of various antigens after intraperitoneal immunization was studied by measuring the levels of circulating antibodies. Injection of BALB/c mice with K11PS resulted in induction of 2-mercaptoethanol-sensitive immunoglobulin M antibodies. The responses observed in BALB/c nu/nu mice and in male (CBA/N X C3H/HeN)F1 mice indicate that K11PS is a thymus-independent type 2 antigen. Immunization of BALB/c mice with either OS-bovine serum albumin or OS-keyhole limpet hemocyanin resulted in the induction of circulating 2-mercaptoethanol-resistant immunoglobulin G antibodies. Results in BALB/c nu/nu mice indicate that the OS-protein conjugates are thymus-dependent antigens. Since the OS-keyhole limpet hemocyanin conjugate induced antibodies in both (CBA/N X C3H/HeN)F1 females and males, we propose to refer to this kind of antigen as a thymus-dependent type 1 antigen, whereas OS-bovine serum albumin, which evoked immunoglobulins in (CBA/N X C3H/HeN)F1 females only, can be referred to as a thymus-dependent type 2 antigen.